2010
DOI: 10.1677/joe-10-0075
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450-mediated 17β-estradiol metabolism in zebrafish (Danio rerio)

Abstract: Cytochrome P4501 (CYP1) and CYP3A proteins are primarily responsible for the metabolism of 17b-estradiol (E 2 ) in mammals. We have cloned and heterologously expressed CYP1A, CYP1B1, CYP1C1, CYP1C2, CYP1D1, and CYP3A65 from zebrafish (Danio rerio) to determine the CYP-mediated metabolism of E 2 in a non-mammalian species. Constructs of each CYP cDNA were created using a leader sequence from the bacterial ompA gene to allow appropriate expression in Escherichia coli without 5 0 modification of the gene. Membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 40 publications
6
61
0
Order By: Relevance
“…By definition, estrogenicity per se is not an adverse effect, as focused, e.g., in females, although disruptions along related pathways often amount to altered homeostasis and regulation of the endocrine system. Compared to the roles of CYP1A and CYP3A in mammalian species, the metabolism of E2 in zebrafish is mainly catalysed by CYP1A and CYP1C enzymes with the formation of 2-hydroxyestradiol (2-OH E2) being the dominant metabolite (Scornaienchi et al 2010). Depending on ligand-activation, both ER and AhR are known to play inhibiting and co-regulating roles in signalling of either pathway (Hasselberg et al 2005, Matthews and Gustaffson 2006, Gräns et al 2010, Ohtake et al 2011, Bugel et al 2013.…”
Section: Er-and Ahr-mediated "Cross Talk" In Endocrine Responsesmentioning
confidence: 99%
“…By definition, estrogenicity per se is not an adverse effect, as focused, e.g., in females, although disruptions along related pathways often amount to altered homeostasis and regulation of the endocrine system. Compared to the roles of CYP1A and CYP3A in mammalian species, the metabolism of E2 in zebrafish is mainly catalysed by CYP1A and CYP1C enzymes with the formation of 2-hydroxyestradiol (2-OH E2) being the dominant metabolite (Scornaienchi et al 2010). Depending on ligand-activation, both ER and AhR are known to play inhibiting and co-regulating roles in signalling of either pathway (Hasselberg et al 2005, Matthews and Gustaffson 2006, Gräns et al 2010, Ohtake et al 2011, Bugel et al 2013.…”
Section: Er-and Ahr-mediated "Cross Talk" In Endocrine Responsesmentioning
confidence: 99%
“…Mouse CYP1B1 was reported to not bind or oxidize 17b-estradiol. The zebrafish enzyme was shown to oxidize estradiol, but, in contrast to the human enzyme that exhibits a 4-hydroxyestradiol (4OH E2)/2-hydroxyestradiol (2OH E2) ratio of approximately 3.44 (Lee et al, 2003), the zebrafish enzyme favored 2-hydroxylation and gave a 4OH E2/2OH E2 ratio of 0.32 (Scornaienchi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The CYP1B1 orthologs from mouse (Savas et al, 1997) and zebrafish (Scornaienchi et al, 2010) have been cloned and heterologously expressed. Mouse CYP1B1 was reported to not bind or oxidize 17b-estradiol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our preliminary screening studies showed high degrees of polymorphism among medaka CYPs and suggested that differing activities of CYP1A and CYP1B1 alleles contribute to differential regulation of sex steroid metabolism between medaka populations from various locations. Indeed, CYP1A and CYP1B1 were highly polymorphic and differentiated across medaka populations, and were also involved in estrogen metabolism in fish [22] ( Figure S1 and Supplemental Experimental Procedures). Therefore, we investigated the role of CYP polymorphisms and the ensuing molecular mechanisms that lead to geographical variations in medaka anal fin morphology, and elucidated the evolution of sexual dimorphisms under CYP genes.…”
mentioning
confidence: 99%